An Analysis of The Implementation of Skimming and Scanning Techniques in SMP Negeri 6 Singaraja - Dewi, Kadek Ayu Astari (Jurnal Penelitian Mahasiswa Indonesia, 2022)
This research was purposed to describe students’ reading comprehension through skimming-scanning technique at SMPN 6 Singaraja and to describe problem in implementing skimming and scanning for the 7th grade students’ reading comprehension in SMPN 6 Singaraja. Descriptive qualitative research is the method employed in this investigation. 1 Teacher and 27 students were the focus subjects of this investigation The result showed that 1) The skimming-scanning technique was implemented in the classroom started from the preparation of the learning which can be seen from the material and the lesson plan and the students are able to understand vocabulary from simple sentence, able to make simple reference by using true false and able to identify main idea from short and simple text. 2) the teacher and student encounter a problem during the implementation of skimming-scanning technique in SMPN 6 Singaraja in which the low ability students have difficulties in understanding the text provided by the teacher and the teacher have to deal with the classroom management in the class.